URGENSI PEMAHAMAN DATA FISIK DAN DATA YURIDIS KEPEMILIKAN HAK ATAS TANAH DI DESA PATTIRO BAJO, KABUPATEN BONE - Farida Patittingi; Muh. Hasrul; Marwah; Amaliyah; Andi Kurniawati (LP2M Universitas Hasanuddin, 2021)
Abstrack. Land disputes between residents are one of the main problems faced by local governments. this is because the land is one of the vital resources in people’s lives. Land issues in the regions require legal certainty to guarantee the quality of community empowerment especially those who own paddy fields and plantations. Land issues in the regions require legal certainty to guarantee the quality of community empowerment especially those who own paddy fields and plantations. This problem occurs because of the lack of community understanding of the importance of land registration, especially regarding the importance of physical and juridical data in land registration. Related to this problem, the solution offered is to conduct socialization activities regarding the importance of physical data and legal data on ownership of land rights. The results achieved in this activity, is the community in the village of Pattiro Bajo understand the urgency of physical data and juridical data on ownership of land rights which is the main foundation in land registration. Land registration is a solution to reduce land disputes between residents so that legal certainty can be guaranteed and improve the quality of village community empowerment. Abstrak. Sengketa pertanahan antar warga merupakan salah satu persoalan utama yang dihadapi pemerintah daerah. Hal ini dikarenakan tanah merupakah salah satu sumberdaya vital dalam kehidupan masyarakat. Persoalan tanah di daerah memerlukan kepastian hukum demi terjaminnya kualitas pemberdayaan masyarakat khususnya yang memiliki tanah persawahan dan perkebunan. Persoalan tersebut terjadi karena kurangnya pemahaman masyarakat mengenai pentingnya pendaftaran tanah khususnya mengenai pentingnya data fisik dan data yuridis dalam pendaftaran tanah. Terkait dengan persoalan tersebut maka solusi yang ditawarkan adalah melakukan kegiatan sosialisasi mengenai pentingnya data fisik dan data yuridis kepemilikan hak atas tanah. Hasil yang dicapai dalam kegiatan ini adalah masya-rakat di Desa Pattiro Bajo memahami mengenai urgensi data fisik dan data yuridis kepemilikan hak atas tanah yang menjadi landasan utama dalam pendaftaran tanah. Pendaftaran tanah merupakan solusi untuk mengurangi sengketa tanah antar warga, sehingga dapat terjaminnya kepastian hukum dan meningkatkan kualitas pemberdayaan masyarakat desa.